Analysis of Industrial Management and Added Value of Tenggiri Fish Pempek, Case Study of IKM Jeol Food Indonesia, Bandung City - Rona Nieki Novaliana; Junianto Junianto (Nekton, 2025)
The fishery product processing industry plays a significant role in enhancing product added value and stimulating local economic growth for national development. However, research related to industrial management and added value in SMEs processing Spanish mackerel pempek remains limited, particularly in the post-COVID-19 pandemic period. This study aims to analyze industrial management and the added value of Spanish mackerel pempek at Jeol Food Indonesia SME in Bandung City. The research employed a survey method, collecting data through observations and interviews with the business owner. Both primary and secondary data were utilized. The analysis encompassed three aspects of industrial management: raw material procurement, production, and marketing, along with added value calculation using the Hayami method, a method designed to measure commodity value enhancement due to functional inputs. Results indicated efficient raw material procurement managed via a pre-order system with two main suppliers ensuring quality and supply continuity. Production processes adhered to Good Manufacturing Practices (GMP) standards, utilizing technology such as planetary mixers and vacuum sealers, along with process layout optimized for operational efficiency. Marketing strategies involved market segmentation, cost-plus pricing, digital promotions, and multi-channel distribution, including exports. Added value analysis revealed that processing 10 kg of minced fish yielded 28.57 kg of pempek, generating an added value of IDR 210,624/kg and a high value-added ratio of 42%. Profit margins reached 52.78%. These findings demonstrate that the processing of Spanish mackerel by Jeol Food Indonesia SME contributes significantly to added value and profitability.